Commonwealth Games and Their Impact on Scotland’s Future in or outside the United Kingdom - Ochman, Katarzyna (International Studies. Interdisciplinary Political and Cultural Journal, 2013)
It is more than probable that the Commonwealth Games in 2014 will be used by the Scottish government as a tool in the battle for independence. For the Scottish National Party (SNP), sport events constitute another opportunity to underline Scottish autonomy. During the last Olympic Games, SNP ministers refused to use the name “Team GB” in their message to the Scottish athletes. Nurturing Scottish pride during the Games has already begun, with the official mascot—the Clyde Thistle, which is Scotland’s national flower and emblem. The mascot of the Commonwealth Games has never waved the patriotic flag as it does now.